A comparison of bone quality and its determinants in young opioid-dependent women with healthy control group. (1st June 2017) - Ding, Zenghui; Chen, Yanyan; Wang, Xi; zhou, Xu; Xu, Yang; Ma, Zuchang; Sun, Yining; Jiang, Ming
Highlights: Long-term opioid dependent in young opioid-dependent women led to low bone quality. No correlation between bone quality and anthropometric characteristics (BH, BW and FFM) in young opioid-dependent women. Low bone quality was determined by heroin intake duration in young opioid-dependent women. Abstract: Background: Little is known about bone quality and its determinants in patients with opioid addiction. The goal of this study was to compare bone quality and its determinants in young opioid addicted women with a local group of young healthy women. Method: Using cross-sectional design, 104 women (mean age 29.9 yrs, range: 20–40 yrs, SD = 7.8) with previous opioid addiction and current methadone substitution (3–30 mg, daily) for 1–16 weeks were compared to 117 healthy women (mean age 31.0 yrs, range: 20–40 yrs, SD = 5.9). Bone quality was examined with quantitative ultrasound. Anthropometric characteristics (body weight, fat free mass (FFM), fat mass) were obtained by bioelectrical impedance analysis. Substance use and other risk factors for low bone quality were assessed by questionnaire-based interviews. Results: More than one-quarter (34%) of patients had osteopenia (n = 31) or osteoporosis (n = 4), compared to 16% of the healthy control group having osteopenia (n = 18). Bivariate correlation analysis demonstrated that age, body weight, and FFM correlated with bone quality (p < 0.05) in healthy women, which were not found in patients. Multivariate analyses showed that in healthy controls, the determinants of bone quality were age, body height, physical activity, and BMI, but in patients, the determinant of bone quality was duration of drug intake. Conclusions: Long-term opioid dependence in young women may lead to low bone quality. Efforts to increase awareness of low bone quality in young opioid addicted women should be considered so that effective treatment may be employed to lower future fracture risk.